Total and Potentially Active Bacterial Communities Entrapped in a Late Glacial Through Holocene Ice Core From Scarisoara Ice Cave, Romania - Paun, Victoria I.; Icaza, Gonzalo; Lavin, Paris; Marin, Constantin; Tudorache, Alin; Perşoiu, Aurel; Dorador, Cristina; Purcarea, Cristina (Frontiers in Microbiology, 2019)
Our understanding of the icy-habitat microbiome is likely limited by a lack of reliable data on microorganisms inhabiting underground ice that has accumulated inside caves. To characterize how environmental variation impacts cave ice microbial community structure, we determined the composition of total and potentially active bacterial communities along a 13,000 year-old ice core from Scarisoara cave (Romania) through 16S rRNA gene Illumina sequencing. An average of 2,546 prokaryotic gDNA operational taxonomic units (OTUs) and 585 cDNA OTUs were identified across the perennial cave ice block and analyzed in relation to the geochemical composition of ice layers. The total microbial community and the putative active fraction displayed dissimilar taxa profiles. The ice-contained microbiome was dominated by Actinobacteria with a variable representation of Proteobacteria, while the putative active microbial community was equally shared between Proteobacteria and Firmicutes. Accordingly, a major presence of Cryobacterium, Lysinomonas, Pedobacter and Aeromicrobium phylotypes homologous to psychrotrophic and psychrophilic bacteria from various cold environments were noted in the total community, while the prevalent putative active bacteria belonged to Clostridium, Pseudomonas, Janthinobacterium, Stenotrophomonas and Massilia genera. Variation in the microbial cell density with the dissolved organic carbon (DOC) content and the strong correlation of DOC and silicon concentrations revealed a major impact of depositional processes on microbial abundance throughout the ice block. Post-depositional processes appeared to occur mostly during the 4,000-7,000 years BP interval. A major bacterial composition shift was observed in 4,500-5,000 year-old ice, leading to a high representation of Beta- and Deltaproteobacteria in the potentially active community in response to the increased concentrations of DOC and major chemical elements. Estimated metabolic rates suggested the presence of a viable microbial community within the cave ice block, characterized by a maintenance metabolism in most strata and growth capacity in those ice deposits with high microbial abundance and DOC content. This first survey of microbial distribution in perennial cave ice formed since the Last Glacial period revealed a complex potentially active community, highlighting major shifts in community composition associated with geochemical changes that took place during climatic events that occurred about 5,000 years ago, with putative formation of photosynthetic biofilms.